Imagen, figura y salvajismo: : una apuesta afectiva desde la práctica artística en la conformación de imaginarios en resistencia (REVISTA NODO, 2026)
This paper contributes to a critical reflection on the scope of the affective as a new paradigm in the study of the contemporary image. In this context we consider the sensitive and collaboration as a new horizon where the emerging paradigm of artistic development is announced. Four visual projects are proposed and analyzed that fundamentally focus on the affective turn as a mode of resistance, in light of Jean François Lyotard's notions of figure and savage.